Efficacy and safety of edoxaban in comparison with dabigatran, rivaroxaban and apixaban for stroke prevention in atrial fibrillation - Skjøth, Flemming; Larsen, Torben Bjerregaard; Rasmussen, Lars Hvilsted; Lip, Gregory Y. H. (Thrombosis and Haemostasis, 2014)
Large Phase 3 clinical trials for stroke prevention in atrial fibrillation (AF) have compared non-vitamin K antagonist oral anticoagulants (NOACs) against warfarin, with the edoxaban trial only recently reported. In the absence of head to head trials directly comparing these NOACs against each other, we compared the efficacy and safety of edoxaban to other agents by an indirect comparison analysis. We performed an indirect comparison analysis of edoxaban (2 dose strategies) against apixaban (1 dose), dabigatran etexilate (2 doses) and rivaroxaban (1 dose), for their relative efficacy and safety against each other. For high-dose edoxaban vs apixaban, there were no significant differences in efficacy endpoints, mortality, myocardial infarction and major bleeding. Apixaban was associated with less major or clinically relevant non-major bleeding (hazard ratio [HR] 0.79; 95% confidence interval [CI] 0.70–0.90) and gastrointestinal bleeding (HR 0.72; 95% CI 0.53–0.99). For dabigatran 110 mg twice daily, there were no significant differences in the main efficacy or safety endpoints. Dabigatran 150 mg bid was associated with lower stroke/systemic embolism (SE) (HR 0.75; 95% CI 0.56–0.99), stroke (HR 0.73; 95% CI 0.55–0.96) and haemorrhagic stroke (HR 0.48; 95% CI 0.23–0.99). There were no significant differences between high-dose edoxaban vs rivaroxaban for efficacy endpoints or mortality, but rivaroxaban had more major and/or clinically relevant non-major bleeding. When compared to low-dose edoxaban, apixaban was associated with lower stroke/SE (HR 0.70; 95% CI 0.55–0.89), stroke (HR 0.70; 95% CI 0.55–0.92) and ischaemic stroke (HR 0.65; 95% CI 0.50–0.89), but more major bleeding (HR 1.47; 95% CI 1.20–1.80). For dabigatran 110 mg bid, there were no significant differences in the efficacy endpoints, but dabigatran 110 mg bid had higher major (and gastrointestinal) bleeding. Dabigatran 150 mg bid and rivaroxaban were associated with lower stroke/SE and ischaemic stroke, but higher bleeding rates. In the present analysis, we have provided for the first time, comparisons of efficacy and safety of edoxaban against other NOACs. Notwithstanding the significant limitations of an indirect comparison analysis, some differential effects are evident with the NOACs for stroke prevention, allowing us to allow the prescriber a ‘choice’ to be able to fit the drug to the patient clinical profile (and vice versa).Note: The review process for this paper was fully handled by Christian Weber, Editor in Chief.
Keywords: Atrial fibrillation; indirect comparisons; stroke prevention; dabigatran; apixaban; rivaroxaban; edoxaban